2016
DOI: 10.1016/j.jnt.2015.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Salajan's conjecture on discriminating terms in an exponential sequence

Abstract: Given a sequence of distinct positive integers v 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…that was first considered in this context by Jerzy Browkin. The case q = 5 was earlier dealt with by Moree and Zumalacárregui [9], who showed that, for this value of q, the smallest positive integer m discriminating u q (1), . .…”
Section: Putmentioning
confidence: 96%
“…that was first considered in this context by Jerzy Browkin. The case q = 5 was earlier dealt with by Moree and Zumalacárregui [9], who showed that, for this value of q, the smallest positive integer m discriminating u q (1), . .…”
Section: Putmentioning
confidence: 96%
“…The value of q * does not play a role in comparing terms u q (i) and u q (j) with i and j of the same parity. For this reason, various results from [11] can be copied (almost) verbatim. In such a case we say that the proof follows by an equal parity index argument.…”
Section: Question 1 Does There Exist a Prime That Is Both Fermat Andmentioning
confidence: 99%
“…. , v(n) are pairwise incongruent modulo m. There are some results regarding the discriminator in case v(j) is a polynomial in j (see [11] and references therein). Beyond the polynomial case, very little is known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the discriminators of various types of functions have been considered by Zieve [10], Sun [8], Moree and Zumalacárregui [6], Haque and Shallit [4].…”
Section: Introductionmentioning
confidence: 99%